Prototype of A/Duck/Sukoharjo/Bbvw-1428-9/2012 subtipe H5N1 clade 2.3.2 as vaccine on local duck - Indriani, Risa; Dharmayanti, NLPI (Indonesian Animal Sciences Society, 2014)
A/Duck/Sukoharjo/Bbvw-1428-9/2012 virus subtipe H5N1 clade 2.3.2 as seed vaccine on local duck. AI H5N1 clade 2.3.2 vaccine containing 256 HAU per dose was formulated using adjuvant ISA 71VG Montanide â¢. Six groups of one day old local duck were used in this study. Three groups (10 ducks per group) were vaccinated and 3 groups (9 duck per group) were served control. Vaccination was conducted when the duck were three weeks old of age using single dose. Three weeks after vaccination when the duck were challenged either with HPAI H5N1 clade 2.3.2, or HPAI H5N1 clade 2.1.3 virus at dose 106 EID50/ 0.1 ml by dropsÂ intranasaly. Result showed that vaccination produced 100% protection compared to unvaccinated ducks againt HPAI subtipe H5N1 clade 2.3.2, and 100% protection againt HPAI H5N1 clade 2.1.3 (A/ck/wj/Subang-29/2007 and A/ck/wj/Smi-Part/2006), while unvaccinated ducks showed virus shedding on day 3 post infection. Key Words: Duck, Influenza, Clade 2.3.2, Vaccine, Clade 2.1.3